Chemical characteristic of new variety of Arabica coffee L. harvested in 2016 in Huatusco, Veracruz-Mexico - González Ríos, Oscar; Suárez Quiroz, Mirna Leonor; Winkler, Robert; Ramírez-Hernández, Ana Karen (Revista Colombiana de Investigaciones Agroindustriales, 2018)
The varieties of coffee resistant to pests and diseases as an alternative use to maintain their production, must first adapt to the soil conditions of the cultivated regions, present an adequate production yield (kg/ha) and contain quality chemical markers, which will impact on the aromatic and sensory profile in your drink. The objective of this work was to characterize chemically the hybrid variety of coffee “Millennium” (H10®), introduced in 2015 in Veracruz, Mexico and compare it with the variety “Typica” (VT). The content of lipids, protein, caffeine, sucrose and 5-O-caffeoyl-quinic acid (5-CQA) was studied in green coffee grains, by classical and chromatographic methods (HPLC); and the volatile fraction in green and roasted grains, was studied by the coupling technique of: HS-SPME-GC-MS and by the direct incidence of plasma ray on coffee beans (UPLC-ESI-MS/MS). The dry matter values of caffeine (0.8g/100g) and sucrose (6.6/100g) in green beans were similar in H10® to those in VT. The content of lipids and 5-CQA, of H10®, showed a significant positive difference of +6.1g and +0.1g per 100g respectively and a significantly lower protein content of -2.5g/100g with respect to the VT. Of a total of 24 volatile organic compounds identified by HS-SPME-GC-SM in roasted samples, only 2-methylpropanal, 3-acetyl-1-methylpyrrole and myrcene, were present in the H10® variety with respect to VT. The study by UPLC-ESI-MS/MS, showed in green and roasted beans a total of 87 more intense ions, where in green coffee, the H10® variety was characterized by 19 ions and the VT by an ion. For roasted coffee, 6 bins between 85.97 and 290.87m/z, characterized the volatile fraction of H10®, while 7 bins between 80.02 and 470.21m/z characterized the volatile fraction of the VT.